Sterilization Practices In Surgical Procedures For Patients With Diabetes: A Scientific Review (The Review of Diabetic Studies, 2024)
The presence of diabetes mellitus greatly predisposes postoperative surgical site infections (SSIs) because of poor immunity, delayed healing of wounds and poor glycemic control. Since the SSIs are one of the most avertable contributors of prolonged hospitalization and post-surgery morbidity, surgical sterilization measures are important to diabetic patients. This system review assesses new sterilization and infection-control practices in the operating room when carrying out operations on diabetic patients. PubMed, Scopus, and Google Scholar of 2020-2024 literature were examined as the articles related to the sterilization conditions, specific infection risk in diabetics, and perioperative care. The results demonstrate that among diabetic patients, sterilization practices are one of the factors that lower the risk of SSI by 35- 55% upon the increase of low-temperature sterilization, reprocessing of instruments, antimicrobial coating, and decolonization before the start of the surgery. Still, it has problems that are associated with inconsistency in its implementation, insufficient personnel training, and non-uniformity in glycemic management practice. Case of the fortification of sterilization processes, as well as diabetes-related perioperative principles, is the key to SSI reduction and better surgical outcomes.